A expansão dos campi federais afeta a economia dos municípios? - Bernicker, Luís Eduardo dos Santos (2018)
In many countries it is observed that investment in knowledge infrastructure through universities is used as an inducer of economic growth for the regions (Goldstein and Renault, 2004). Thus, the article aims to investigate the expansion policy of the federal campuses held between the years 2000 to 2012 for all municipalities that have benefited from this policy. The effects of the opening of campuses will be measured on economic growth through the logarithm of real GDP per capita, and on the proportion of workers in the service sector, commerce, manufacturing industry and all sectors together. The study period covers two official expansion policies, the first one started in 2003 and was the Phase I Expansion Program that lasted until 2007. The second was the REUNI (Restructuring and Expansion of Federal Universities) that ran from 2007 to 2012. Both plans had as objective the expansion in the number of universities and federal campuses. In the meantime, REUNI focused on expanding existing universities' infrastructures. In 2000, Brazil had 39 universities and 73 federal campuses, and in 2012, the number moved to 59 universities and 219 campuses, more than doubling the number of campuses in the country. It should be noted that most of the municipalities that received new federal campuses are located in the interior of the country, receiving approximately 84% of the new campuses created during this period. The method used was that of difference-differences with propensity score matching that allows to identify the effect of public policy controlling for observable and unobservable characteristics. The results show that there were no positive and significant impacts on the average log of real GDP per capita and the proportion of workers in the manufacturing industry of those municipalities that received a new federal campus, however, in the services, commerce and when analyzed all sectors together is observed a positive effect on the creation of new jobs.